2014
DOI: 10.1016/j.ejar.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Microbial assessment and prevalence of antibiotic resistance in polluted Oluwa River, Nigeria

Abstract: Antibiotics are emerging environmental contaminants, causing both short-term and long-term alterations of natural microbial communities due to their high biological activities. The antibiotic resistance pattern of bacteria from anthropogenic polluted Oluwa River, Nigeria was carried out. Microbial profiling and antibiotic sensitivity tests were carried out on water and sediment samples using 13 different antibiotics. Microorganisms isolated include those in the genera Bacillus, Micrococcus, Pseudomonas, Strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 37 publications
6
35
0
2
Order By: Relevance
“…Thus in its present form, it is unsafe for human use (Table 3). This result is similar to that of Omoigberale et al (2014) and that of Ayandiran et al (2014). The former results revealed that the bacterial counts were shown to be highest in the rainy season and the least total viable counts were recorded in the month of January with total coliform counts ranged from 27 MPN/100 ml to 350 MPN/100 ml while the faecal coliform counts from 5 MPN/100 ml to 26 MPN/100 ml.…”
Section: Microbial Water Qualitysupporting
confidence: 80%
“…Thus in its present form, it is unsafe for human use (Table 3). This result is similar to that of Omoigberale et al (2014) and that of Ayandiran et al (2014). The former results revealed that the bacterial counts were shown to be highest in the rainy season and the least total viable counts were recorded in the month of January with total coliform counts ranged from 27 MPN/100 ml to 350 MPN/100 ml while the faecal coliform counts from 5 MPN/100 ml to 26 MPN/100 ml.…”
Section: Microbial Water Qualitysupporting
confidence: 80%
“…[1]. Water is an indispensable resource for supporting life systems [2][3][4], while access to safe drinking water is a basic human right, which is essential for healthy life [5][6][7]. Globally, about 1.1 billion people lack access to improved water supplies [8].…”
mentioning
confidence: 99%
“…Water samples in this study were collected from 3 different sites along the stream during wet season, samples were taken 10cm below the water surface and collected in 150ml glass screw-capped containers than transported to the laboratory in ice boxes and analyzed within 24 hours [6]- [7].…”
Section: Methodsmentioning
confidence: 99%